2017
DOI: 10.1080/15438627.2017.1282359
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical, metabolic and cardiopulmonary responses of masters recreational runners during running at different speeds

Abstract: This study tested interactions between age and running speed on biomechanics, metabolic responses and cardiopulmonary responses. Three-hundred participants ran at preferred and standardized speeds. Age group (younger, masters [≥40 years]) by speed (self-selected 8.8 km/h, 11.2 km/h and 13.6 km/h) interactions were tested on main outcomes of sagittal kinematic, temporal spatial, metabolic and cardiopulmonary parameters. At all speeds, angular displacements of the ankle, pelvis and knee were less in masters than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Running with more knee flexion at touch-down and a larger knee joint range of motion has been linked to a higher metabolic demand—i.e., a worse running economy ( 50 52 ). Previous studies have found older runners to run with a more flexed knee at touch-down and a smaller knee joint range of motion ( 22 , 25 , 47 ), which would respectively contribute to a worse and better running economy, and thus a negligible net change. In our study, however, master runners only ran with a less flexed knee at touch-down but had a similar knee range of motion to young runners, which together would contribute to a better running economy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Running with more knee flexion at touch-down and a larger knee joint range of motion has been linked to a higher metabolic demand—i.e., a worse running economy ( 50 52 ). Previous studies have found older runners to run with a more flexed knee at touch-down and a smaller knee joint range of motion ( 22 , 25 , 47 ), which would respectively contribute to a worse and better running economy, and thus a negligible net change. In our study, however, master runners only ran with a less flexed knee at touch-down but had a similar knee range of motion to young runners, which together would contribute to a better running economy.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in running kinematics and performance have indeed been linked previously in short- ( 23 ) and middle-distance ( 24 ) runners. However, trained master runners have also been shown to maintain a similar running economy at sub-maximal speeds compared to young runners, despite having distinct biomechanical characteristics ( 21 , 25 ). Although running economy and performance are influenced by numerous factors, it is yet unclear how this apparent paradox can be explained.…”
Section: Introductionmentioning
confidence: 99%